2021
DOI: 10.1002/ejp.1785
|View full text |Cite
|
Sign up to set email alerts
|

Neck and shoulder pain in adolescents seldom occur alone: Results from the Norwegian Ungdata Survey

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
2
4
0
2
Order By: Relevance
“…In Norway, similar findings were shown wherein health surveys revealed that one-third of adolescents aged 13-18 years had pain occurring weekly for the last 3 months [5]. In a more recent study including Norwegian adolescents, 24% of adolescents reported neck/shoulder pain; these adolescents also tended to report depression and other co-occurring pain problems [6]. The high prevalence of pain in adolescence and the corresponding potential high future costs in society highlight the importance of identifying determinates for pain in adolescence.…”
Section: Introductionsupporting
confidence: 63%
“…In Norway, similar findings were shown wherein health surveys revealed that one-third of adolescents aged 13-18 years had pain occurring weekly for the last 3 months [5]. In a more recent study including Norwegian adolescents, 24% of adolescents reported neck/shoulder pain; these adolescents also tended to report depression and other co-occurring pain problems [6]. The high prevalence of pain in adolescence and the corresponding potential high future costs in society highlight the importance of identifying determinates for pain in adolescence.…”
Section: Introductionsupporting
confidence: 63%
“…In these participants, the probability of having neck pain at follow-up was 67% (95% CI [65–70]) among the girls and 50% (95% CI [ 47 53 ]) among the boys. This was compared to 13% (95% CI [ 12 15 ]) among the girls and 7% (95% CI [ 6 8 ]) among the boys with moderate to high physical activity level, not feeling lonely and no headache/migraine, back pain or neck/shoulder pain.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, neck pain become persistent in many adolescents, but there is little knowledge regarding risk factors and causes of neck pain in these individuals [ 5 ]. The high prevalence of neck pain in adolescents [ 2 , 6 ] is of great concern since studies suggest that individuals who develop pain and disabilities during adolescence are more likely to report these health complaints in adulthood [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents in the latter category were those who answered “every day” to at least one of the six items [ 24 ]. This approach is recommended by the Ungdata project leader to capture severe physical health complaints [ 25 ] The six variables as an indicator for physical health problems are used in several waves of the survey, but are not formally validated or reliability tested [ 26 ].…”
Section: Methodsmentioning
confidence: 99%